Pengaruh Lokasi, Harga dan Kualitas Produk Terhadap Minat Beli Rumah Hunian di Singhasari Residence (Studi Pada Masyarakat Penghuni Singhasari Residence) - Muh. Mushoffa Nufail; Agus Widarko; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This research is motivated by the rapid population growth in Singosari District, which has triggered a high demand for housing, making it essential for developers to understand the factors influencing consumer purchase interest. Employing a quantitative approach with a causal associative method, this study involved 55 respondents from the Singhasari Residence community, selected through simple random sampling. Data were analyzed using multiple linear regression via SPSS software to examine the effects of location, price, and product quality. The primary findings indicate that, simultaneously, these three variables significantly influence purchase interest, contributing 61.3% to the variance. Partially, location and price have a positive and significant impact due to strategic accessibility and competitive economic value, whereas product quality does not show a significant effect due to the perceived uniformity of building standards. In conclusion, purchase interest at Singhasari Residence is predominantly driven by location and price factors; therefore, developers are advised to continuously optimize pricing strategies and accessibility advantages to maintain market attractiveness. Keywords: Location, Price, Product Quality, Purchase Interest, Singhasari Residence.